A cost‐effective adaptive random testing approach by dynamic restriction. Issue 6 (1st December 2018) - Ackah-Arthur, Hilary; Chen, Jinfu; Xi, Jiaxiang; Omari, Michael; Song, Heping; Huang, Rubing
Abstract : A key objective of software testing is to find program errors that cause failure in software, at less cost. One basic testing technique is random testing (RT), but many researchers have criticised its failure‐detection effectiveness. Several researchers have proposed that an enhancement of the failure‐detection effectiveness of RT is achieved if test cases are evenly spread within the input domain. Adaptive RT (ART) describes a family of algorithms that employ various strategies to evenly and randomly spread test cases. Fixed sized candidate set ART (FSCS‐ART) is an ART algorithm that has gained many research studies far and wide; however, the high distance computations make its algorithm computationally expensive. The authors propose a new ART method that restricts distance computations to only test cases inside an exclusion zone. The experimental results show that the new ART method not only improves RT but also provides failure‐detection effectiveness similar to FSCS‐ART, while significantly minimising computation overhead.